The Effectiveness of the Learning Using Play-learning Method in Recognizing the Concept of Numbers Ranging From 1 To 9 Among Hearing Impaired Children - Yuni Fazilawati Binti Md Yusof (Best Practices in Disability-Inclusive Education, 2023)
This survey aims to look how effective is learning through playing in teaching and learning Mathematics with ‘the concept of numbers from 1 to 9’ among special education pupils with hearing problems. The study was carried out in an integration school program with hearing impaired at SK Tengku Indera Petra, Kota Bharu, Kelantan. This study was carried out for 6 weeks. A total of 20 pupils at Level One were selected for this survey as sample of study. For Mathematics, recognizing the concept of numbers from 1 to 9 is one importance basic skills to develop their cognitive skills in special education of hearing-impaired pupils. To increase the level of the concept numbers, the methods of learning through playing was chosen because the process of teaching and learning is exciting and fun. The teaching and learning process was done by using four games as ‘Permainan Batu Seremban’, Dream Wheel, Number Bowling and Poison Box. The study had achieved the target and fulfilled the objectives 80% of the respondents had achieved the target where they are able to understand and able to answer the questions correctly and satisfactory. This method, ‘learning through playing’ could attract the respondent and gave some fun for the respondent to continue learning. It could also stimulate the interest of respondent to understand the concept easily. The overall activities and the final exam had proved that the effectiveness of learning through playing could improve the respondent performance in Mathematics.